Proficiency Enhancement of KVK-Scientists: Illustrating the Capacity Development Needs in Andhra Pradesh and Tamil Nadu - Geetha M; Ananthan P.S.; Bhaskaran A; Shivaji D Argade; Naila M Bhat (Journal of Indian Fisheries Association, 2024)
Krishi Vigyan Kendras (KVK) provide a basket of extension and advisory services and act as bridge between research and extension systems at the district level. The present study assessed the information and training needs of 62 SMSs of the KVKs in Andhra Pradesh and Tamil Nadu through an online survey. Training needs were collected on a three-point continuum scale and ranked using the Weighted Sum Method (WSM). The majority of the respondents were men and belonged to the age group of